A process-based perspective on strategic planning: the role of alternative generation and information integration - Philip Meissner (Business Research, 2014)
To help bridge the gap between the emergent and rational school of strategy formation, I analyze the role of alternative generation and information integration as two process-based characteristics of the strategy process in the relationship between strategic planning and decision quality. Based on a survey of 155 top executives from German small and medium-sized companies, I show that the degree to which multiple alternatives are developed and information is integrated in the planning process mediates a large proportion of the relationship between strategic planning and decision quality. This suggests that a closer analysis of process characteristics in the analysis of strategic planning may help mitigate the divergent results in strategic planning research.
Keywords: M10; L21; L22; 330; Strategic planning; Alternative generation; Information integration; Decision quality; Strategy process; Planned emergence; Process-based characteristics; Strategy process outcome